8.7k views
4 votes
-2(4x + -4) - 3x - 2 =34

2 Answers

4 votes

Answer:

x= -28/11

Explanation:

Multiply -2 by 4x +4

That equals -8x+8

So the equation is now

-8x+8+3x -2 = 34

Now combine like terms

11x+6=34

Subtract 6 from both sides

11x=28

divide by 11 on both sides

x = -28/11

User DasBoot
by
4.7k points
7 votes

Answer:

x = -28/11

Explanation:

-2(4x + -4) - 3x - 2 =34

Distribute

-8x+8 -3x-2 =34

Combine like terms

-11x +6 = 34

Subtract 6 from each side

-11x+6-6 = 34-6

-11x = 28

Divide each side by -11

-11x/-11 = 28/-11

x = -28/11

User FeelGood
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.